Megállapítási és marasztalási perek összehasonlítása, megállapítási keresetek speciális feltételei - Kiss, Szilvia (Debreceni Jogi Műhely, 2014)
For the first, I think that it is necessary to make clear what action is. The action the application to the proposal of which the half interested in the debate is entitled and the court passes judgement on it. Bringing an action to the court is the prerequisite of the setting in motion of the civil action procedure. The plaintiff asks it for the restoration of his violated subjective right practically in the action of detaining to oblige the defendant. The object of the action of detaining the claim originating from the violated subjective right, the controversial material legal contractual relationship, his content though the plaintiff’s application, that let the court oblige it defendant onto a particular activity, abstaining from it. Basic rule: action of detaining expired in case of claims only enforceable. The action of assessment in so much action of detaining, that it positively aims at the court establishing it for the plaintiff’s right and the existence of the defendant’s asking to stay being mentioned. It being possible to initiate action of assessments has two conditions conjunctive: the legal defence for the claim of his necessity and the impossibility of the vindication. The content and the consequences of the action of assessment considering too narrower than the action of detaining. The plaintiff’s aim in the action of assessment, that the court clears up whether one of the contractual relationships exist with a judgement or not, it does not claim him accomplishing a defendant’s active behaviour beyond this. The deficiency of the execution follows from this, the giving onto an end which can be grown in the part of a judgement saying detaining in the legal charge only. Verifiable, that the action of assessment independent legal defence device quality actions. Categorically cannot be declared, if action of detaining possible, assessment one is not eligible. The clarification of the situation and correcting him wait for the legislator however.